Browsing is a strong filter for savanna tree seedlings in their first growing season - Archibald, S; Twine, W; Mthabini, C; Stevens, N (Wiley, 2021)
Newly germinated seedlings are vulnerable to biomass removal but usually have at least six months to grow before they are exposed to dry-season fires, a major disturbance in savannas. In contrast, plants are exposed to browsers from the time they germinate, making browsing potentially a very powerful bottleneck for establishing seedlings.